Beyond paradise. Series two [videorecording (DVD)] - Thorogood, Robert; Jordan, Tony, 1957- (BBC Studios, 2024)
Shipton Abbott continues to keep DI Humphrey Goodman and his team busy, with a baffling crime each week, from a death on a steam train to a missing teacher. Meanwhile, Humphrey and Martha's journey to find their own version of a family continues as they explore the possibility of fostering. Martha's mother Anne throws herself into the world of online dating. And a well-meant gesture from Esther's daughter Zoe threatens to uncover a long-held secret. Includes the 2023 Christmas special.